Life and Society in Byzantine Cappadocia - Cooper, Eric. author. aut Link
XIV, 339 p.
Keywords: This is the first in-depth historical study of Byzantine Cappadocia. The authors draw on extensive textual and archaeological materials to examine the nature and place of Cappadocia in the Byzantine Empire from the fourth through eleventh centuries.